PENGARUH GREEN INNOVATION STRATEGIC ORIENTATION DAN DIGITAL TECHNOLOGY IMPLEMENTATION TERHADAP GREEN COMPETITIVENESS: PERAN MEDIASI GREEN INFORMATION PROACTIVENESS, TRANSPARENCY, DAN FORMALITY PADA UMKM DI MADURA - Imam, Achmad; Hamzah, Moh; Wulandari, Sri; Aini, Sumratih; Anggraeni, Meilinda; Zainurrafiqi, Zainurrafiqi (Al-Amien Prenduan University, Sumenep, 2025)
This study examines the influence of Green Innovation Strategic Orientation (GISO) and Digital Technology Implementation (DTI) on Green Competitive Advantage (GCA) in Micro, Small, and Medium Enterprises (MSMEs) in Madura, focusing on the mediating role of Green Information Proactiveness, Transparency, and Formality. The study aims to address the challenges faced by MSMEs in adopting green innovation and digital technologies, particularly in Sampang and Sumenep, where digital literacy and environmental transparency remain low. A quantitative approach was employed, using a structured questionnaire distributed to 493 MSME managers in Sampang and Sumenep. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software to assess direct and indirect relationships among the variables. The findings indicate that both GISO and DTI significantly enhance GCA, with Green Information Proactiveness, Transparency, and Formality mediating these relationships. This study contributes to understanding how the integration of green strategies and digital technology can strengthen MSMEs’ competitive advantage while addressing gaps in the literature on green information management. By integrating three dimensions of green information as mediators, this research provides a more comprehensive understanding of GISO and DTI’s contribution to GCA in MSMEs. This approach is particularly relevant for MSMEs in regions with limited access to advanced technology and green information systems. The study offers practical implications for policymakers and MSME managers by emphasizing the importance of fostering green innovation and digital transformation. Future research is recommended to explore the role of external stakeholders and more advanced technologies in further enhancing sustainable competitiveness.